2021
DOI: 10.1101/2021.02.08.430369
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exosomes from COVID-19 patients carry tenascin-C and fibrinogen-β in triggering inflammatory signals in distant organ cells

Abstract: SARS-CoV-2 infection causes cytokine storm and overshoot immunity in humans; however, it remains to be determined whether genetic material of SARS-CoV-2 and/or virus induced soluble mediators from lung epithelial cells as natural host are carried out by macrophages or other vehicles at distant organs causing tissue damage. We speculated that exosomes as extracellular vesicles are secreted from SARS-CoV-2 infected cells may transport messages to other cells of distant organs leading to pathogenic consequences. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 38 publications
(52 reference statements)
0
18
0
Order By: Relevance
“…Plasma exosomes from COVID-19 infected patients contains high level of tenascin-C (TNC) and fibrinogen-β (FGB) compared to that of healthy normal controls. Both TNC and FGB stimulate pro-inflammatory cytokines via NF-κB pathway ( 216 ). Exosomes contains non-coding RNAs play a crucial role in virus mediated disease progression.…”
Section: Role Mechanism and Management Of Exosomes In Treatment Of Sars-cov-2 Infected Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma exosomes from COVID-19 infected patients contains high level of tenascin-C (TNC) and fibrinogen-β (FGB) compared to that of healthy normal controls. Both TNC and FGB stimulate pro-inflammatory cytokines via NF-κB pathway ( 216 ). Exosomes contains non-coding RNAs play a crucial role in virus mediated disease progression.…”
Section: Role Mechanism and Management Of Exosomes In Treatment Of Sars-cov-2 Infected Patientsmentioning
confidence: 99%
“…The presence of TNC and FGB in SARS-CoV-2 infected patient exosomes may be a mechanism for cytokine storm resulting in micro-thrombosis in some patients and TNC and/or FGB can be used as the potential prognostic markers for COVID-19 patients. TNC and FGB-enriched exosomes from COVID-19 plasma and may be correlated for the first time with pathogenesis ( 216 ) Fujita et al. reported that antiviral response-related EV proteins, coagulation-related markers, and liver damage-related exRNAs serving as potential early predictive biomarkers for COVID-19 severity ( 217 ).…”
Section: Role Mechanism and Management Of Exosomes In Treatment Of Sars-cov-2 Infected Patientsmentioning
confidence: 99%
“…Exosomes have also recently emerged as efficient platforms for immunomodulation in the tumor microenvironment and other tissue contexts (131,215); it is likely that the prominent roles TnC has as a regulator of immune cell function (see first section) are exerted at least in part through exosomes. Interestingly, exosomes released by SARS-CoV2-infected cells are significantly enriched in TnC and could promote the propagation of inflammation to distant sites (216). Serum TnC levels have been explored as diagnostic/prognostic markers in different pathologies (24), but whether all circulating TnC is exclusively trafficked through EVs is yet to be determined.…”
Section: Ev Secretion: An Integral Aspect Of Tnc Biological Rolesmentioning
confidence: 99%
“…Involving regulation of immunity [114,115], in ammatory cytokines [114,[116][117][118][119][120], pulmonary brosis [121], and virus infection, e.g., SARS-CoV-2, H1N1 [115][116][117][119][120][121][122][123][124] Cytokine-cytokine receptor interaction…”
Section: Kegg Pathway Potential Role During Sars-cov-2 Infection Induced By Reported Evidence Nf-kappa B Signaling Pathwaymentioning
confidence: 99%